2014
DOI: 10.3390/v6125135
|View full text |Cite|
|
Sign up to set email alerts
|

Progressive Adaptation of a CpGV Isolate to Codling Moth Populations Resistant to CpGV-M

Abstract: The NPP-R1 isolate of CpGV is able to replicate on CpGV-M-resistant codling moths. However, its efficacy is not sufficient to provide acceptable levels of control in natural (orchard) conditions. A laboratory colony derived from resistant codling moths was established, which exhibited a homogeneous genetic background and a resistance level more than 7000 fold. By successive cycles of replication of NPP-R1 in this colony, we observed a progressive increase in efficacy. After 16 cycles (isolate 2016-r16), the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 16 publications
2
29
0
4
Order By: Relevance
“…For CpRR1, it was demonstrated that resistance-breaking properties of the CpGV isolates depended on the lack of an insertion of 24 bp in the open reading frame (ORF) pe38 in CpGV-M (group A), which is missing in all resistance-breaking isolates of genome group B to E CpGVs (6). By registration of some of these isolates, a successful commercial control of the type I resistance in C. pomonella was eventually reestablished in Europe (23)(24)(25)(26)(27)(28).…”
Section: Importancementioning
confidence: 99%
“…For CpRR1, it was demonstrated that resistance-breaking properties of the CpGV isolates depended on the lack of an insertion of 24 bp in the open reading frame (ORF) pe38 in CpGV-M (group A), which is missing in all resistance-breaking isolates of genome group B to E CpGVs (6). By registration of some of these isolates, a successful commercial control of the type I resistance in C. pomonella was eventually reestablished in Europe (23)(24)(25)(26)(27)(28).…”
Section: Importancementioning
confidence: 99%
“…It was expected that CpGV resistance in other regions in Europe would follow a mode similar to that of CpRR1, because (i) a Z-chromosomal dominant inheritance was determined for several widely separated CM populations in Germany, France, and the Czech Republic (13,19,25,26); and (ii) the resistant CM populations in Europe were susceptible to resistance-breaking CpGV isolates, several of which have been registered and used as new CpGV products in Europe (10,21,22,(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Resistance to the first strain was overcome, in a practical sense, with a new resistancebreaking variant that had a different resistance mechanism (Eberle et al, 2008;Berling et al, 2009;Graillot et al, 2014). However, very recently, some populations were able to break resistance again and achieve cross resistance to the second strain of CpGV with dominant autosomal inheritance (Sauer et al, 2017a); and a third resistance mechanism has also been identified (Sauer et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%